Megajournals and what they mean for the future of scientific publishing - Pattinson, Damian (Septentrio Conference Series, 2014)
Since it launched five years ago, PLOS ONE has redefined the scientific journal. The broad publication criteria and lack of page limit allowed PLOS ONE to grow at a rate never seen before in the industry, to a level where it needed its own category: the Megajournal. Recently, other publishers have sought to emulate the success of PLOS ONE with releases of their own megajournals. These new journals all have similar properties: full Open Access, editorial criteria based on sound science and not on significance or impact, fast turnaround, broad scope. In this talk I shall discuss the features of megajournals, their benefits and weaknesses, and what their arrival means for the future of scientific publishing.